Instruction design and educational quality - Abbas Alzand, Walid Khudhur (Elsevier, 2010)

(untitled)
The problems facing the quality of Educational system in Arab World are not much different from those encountered by other educational systems in the developing countries. The instructional design (ID) is a new approach which emphasizes on thinking as an aim of education, and also as a contract between the learners, teacher, time instruction, subject matter and learning environment. The aim of this paper is to present the ten years researches effort in the field of learning and instruction design conducted in several Arab countries. This study set to prove the relationship between the usage of ID and the quality of education.